A Taxonomy of Tasks for Assessing the Impact of New Technologies on Work - Enrique Fernández-Macías; Martina Bisello (European Commission, Joint Research Centre (JRC), 2020)
In recent years, the increasing concern about the labour market implications of technological change has led economists to look in more detail at the structure of work content and job tasks. Incorporating insights from other traditions of task analysis, in particular from the labour process approach (Braverman, 1974), as well as from recent research on skills, work organisation and occupational change (see for instance Green, 2013; Cohen, 2016; Fernández-Macías and Hurley, 2017), in this paper we propose a new comprehensive and detailed taxonomy of tasks. Going beyond existing broad classifications, our taxonomy aims at connecting the substantive content of work with its organisational context by answering two key questions: what do people do at work and how do they do their work? For illustrative purposes, we show how our approach allows a better understanding of the impact of new technologies on work, by accounting for relevant ongoing transformations such as the diffusion of artificial intelligence and the unfolding of digital labour platforms.
Keywords: 330; tasks; technological change; occupations; labour markets; structural change; artificialintelligence; digital labour platforms; Europe